Securing democracies : defending against cyber attacks and disinformation in the digital age / edited by Scott J. Shackelford, Frédérick Douzet, Christopher Ankersen. - Shackelford, Scott J.; Douzet, Frédérick; Ankersen, Christopher (Cambridge University Press, 2026)
Securing Democracies examines the attacks on voting processes and the broader informational environment in which elections take place. The volume's global cadre of scholars and practitioners highlight the interconnections among efforts to target vulnerable democratic systems and identify ways to prevent, defend against, and mitigate their effects on both the technical and the informational aspects of cybersecurity. The work takes a wider view of defending democracy by recognizing that both techniques-attacking infrastructure and using misinformation and disinformation-are means to undermine trust and confidence in democratic institutions. As such, the book proposes a wide range of policy responses to tackle these cyber-enabled threats focusing on the geopolitical front lines, namely Eastern Europe, the Middle East, and East Asia. This title is also available as open access on Cambridge Core.